2016
DOI: 10.1111/voxs.12271
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and motivations to voluntary blood donation in sub‐Saharan African settings: a literature review

Abstract: Background and Objectives Voluntary blood donor recruitment and retention in sub‐Saharan Africa needs to be strengthened. To do this, an understanding of the factors underpinning people's willingness or refusal to donate is essential; yet there has been little attention to these in sub‐Saharan African contexts. This overview of studies explores attitudes of blood donors, non‐donors and potential donors towards voluntary blood donation in a range of sub‐Saharan African settings. Materials and Methods A structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
(122 reference statements)
3
17
0
Order By: Relevance
“…Our results are consistent with the global literature and do not support the idea that donor motivations are different in Africa. In sub‐Saharan studies reviewed by Burzynksi et al, “Saving the life of another person” was the most widely cited motivation for donation and these most often linked to family members, a friend, or replacement donor. Health‐related motivations were recurrently reported as a motivating factor as well as knowledge‐related motivations, such as awareness of blood shortage, having adequate information, or being “directly asked.” In our study, donors were generally in agreement that incentives did not motivate them, and less than 40% said that they donated because they were asked by friends, family, or coworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with the global literature and do not support the idea that donor motivations are different in Africa. In sub‐Saharan studies reviewed by Burzynksi et al, “Saving the life of another person” was the most widely cited motivation for donation and these most often linked to family members, a friend, or replacement donor. Health‐related motivations were recurrently reported as a motivating factor as well as knowledge‐related motivations, such as awareness of blood shortage, having adequate information, or being “directly asked.” In our study, donors were generally in agreement that incentives did not motivate them, and less than 40% said that they donated because they were asked by friends, family, or coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…The main deterrents were fear due to lack of knowledge and discouraging spiritual, religious, and cultural perceptions of blood donation. A literature review of 22 studies on barriers and motivation in sub‐Saharan Africa by Burzynski et al found the main barriers related to health concerns, fears, and lack of knowledge, with sociocultural and practical barriers less dominant deterrents. Saving a relative, friend, or other person's life and access to adequate information were motivators for donation, while an eagerness to receive a range of incentives besides money was widely reported.…”
mentioning
confidence: 99%
“…Recent systematic reviews of the literature have focused on SSAs in their birth countries rather than on those living as ethnic minorities or migrants in Western countries (Tagny et al, ; Burzynski et al, ). According to the qualitative syntheses in these systematic reviews, health‐ and knowledge‐related barriers are commonly cited by SSAs.…”
mentioning
confidence: 99%
“…This topic has been partially reviewed in 2010, but the article mostly focused on safety rather than blood donation and supply (Tagny et al, ). Two more recent reviews of motivators and barriers to blood donation in SSA examined 15 and 22 studies, respectively published between 1982 and 2013 or after 2000 (Burzynski et al, ; Zanin et al, ). The second study was focused on VNRDs where a majority of donations in SSA comes from family/replacement donors (FRD).…”
Section: Resultsmentioning
confidence: 99%